1995
DOI: 10.1136/thx.50.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Multiple brushings with immediate Riu's stain via flexible fibreoptic bronchoscopy without fluoroscopic guidance in the diagnosis of peripheral pulmonary tumours.

Abstract: (2)) than the nine benign lesions (5 (4)).Conclusions -This technique provides a high diagnostic yield, avoids the need for fluoroscopy, and is probably safer than percutaneous biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(1 reference statement)
0
11
0
Order By: Relevance
“…This has been previously reported [6,7,10], mainly in the absence of endoluminal lesions, or when only infiltrative or compressive mucosal changes are seen endoscopically [27]. False positive cytological results are rare, in the order of 0-1.4% [7,9,28,29]; this is an important concept since, due to lack of surgical tissue for most of our patients, we could not assess the positive predictive value (PPV) of these cytologically positive but biopsy-negative specimens. Therefore, we believe that such results consist of false negatives on biopsy.…”
Section: Discussionmentioning
confidence: 57%
“…This has been previously reported [6,7,10], mainly in the absence of endoluminal lesions, or when only infiltrative or compressive mucosal changes are seen endoscopically [27]. False positive cytological results are rare, in the order of 0-1.4% [7,9,28,29]; this is an important concept since, due to lack of surgical tissue for most of our patients, we could not assess the positive predictive value (PPV) of these cytologically positive but biopsy-negative specimens. Therefore, we believe that such results consist of false negatives on biopsy.…”
Section: Discussionmentioning
confidence: 57%
“…12 However, there was also no information about the characteristics of the lesion. Lee et al 13 showed a rate of 86% in the diagnosis of peripheral pulmonary tumors with the technique of immediate cytologic examination of multiple brushings using the Riu stain. In this study, tumor size did not affect the diagnostic yield (83% for r3 cm, 88% for >3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Riu9s stain, modified from Wright9s stain, was first introduced for blood smear staining in 1956 and has been widely used for varied cytological examinations [20]. It takes only 90 s to complete a staining procedure with Riu9s method and the diagnostic accuracy is equal to that achieved with Papanicolaou9s stain when diagnosing pulmonary malignancies [21].…”
Section: Discussionmentioning
confidence: 99%